Pelatihan Teknik Pengecoran Aluminium Bagi Usaha Pengepul Barang Bekas Di Kecamatan Poasia Kota Kendari - Sudarsono Sudarsono; Aminur Aminur; Budiman Sudia; Nanang Endriatno; La Ode Ahmad Barata (Jurnal Pengabdian Masyarakat Ilmu Terapan, 2022)
Handling of used aluminum has been carried out by collectors, namely the compression process. The pressing process is less economical because it still produces cavities and the selling price is low. The purpose of this community service activity is to provide training on Aluminum smelting with casting techniques for two groups of independent collectors, Mandiri Berkah and Maju Jaya. The activity took place in the Mandiri Berkah collector area which was attended by Mandiri Berkah and Maju Jaya employees and the community around Poasia. The method of implementing the activity is a theoretical explanation of Aluminum and its processing method with casting techniques. Used aluminum cans are melted in a charcoal-fired crucible furnace. The used aluminum cans are put in the kowi which is placed in a hot furnace. After the cans are melted, they are poured into rectangular molds. The results of the service activities that resulted were the opening of knowledge insights related to used aluminum. Participants were able to recycle Aluminum by casting technique into ingot products.Keywords: Training, foundry, aluminum, collectors